2018
DOI: 10.1038/s41393-018-0139-2
|View full text |Cite
|
Sign up to set email alerts
|

A validity study of the Spanish—World Health Organization Quality of Life short version instrument in persons with traumatic spinal cord injury

Abstract: The Spanish version of the WHOQOL-BREF questionnaire is useful and reliable to evaluate the quality of life of persons with spinal cord injuries in our population of Spanish-speaking people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Each item on this scale was scored on a 5-point Likert scale (1–5). After the data were collected, the raw domain scores were transformed linearly to a 0–100 scale, with a scoring of 60 points or higher denoting better QoL (Salvador-De La Barrera et al, 2018; The WHOQoL Group, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Each item on this scale was scored on a 5-point Likert scale (1–5). After the data were collected, the raw domain scores were transformed linearly to a 0–100 scale, with a scoring of 60 points or higher denoting better QoL (Salvador-De La Barrera et al, 2018; The WHOQoL Group, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The collaborative assessment of the WHOQOL-BREF scale in 15 cultural settings over several years confirmed good internal consistency (Cronbach's alpha coefficients for the domain scores ranged from 0.66 to 0.84) [6]. Also, assessment of the WHOQOL-BREF in some countries (Brazil, Iran, Spain) confirmed good internal consistency (Cronbach's alpha coefficient > 0.7) [9,13,14]. Most of the validation studies revealed a four-factor structure of the WHOQOL-BREF scale [6,11,15].…”
Section: Introductionmentioning
confidence: 97%
“…In relation to QoL, the application of the WHOQOL-BREF questionnaire in other countries to assess the QOL of persons with SCI has been extensively reported 2 . The Spanish version of the WHOQOL-BREF questionnaire is useful and reliable to evaluate the QoL of persons with SCIs in our population of Spanish-speaking people as reported in a recent study 2 …”
Section: Methodsmentioning
confidence: 84%
“…Current treatment and rehabilitation protocols have improved life expectancy for people with TSCI regardless of their varying degrees of disability. However, achieving a satisfactory quality of life (QoL) is conditioned by the individual’s physical and psychological health, as well as the surrounding socioeconomic factors 2 …”
mentioning
confidence: 99%
See 1 more Smart Citation